Ebola Virus VP35 Interaction with Dynein LC8 Regulates Viral RNA Synthesis - Luthra, Priya (J Virol, 2015)
Ebola virus VP35 inhibits alpha/beta interferon production and functions as a viral polymerase cofactor. Previously, the 8-kDa cytoplasmic dynein light chain (LC8) was demonstrated to interact with VP35, but the functional consequences were unclear. Here we demonstrate that the interaction is direct and of high affinity and that binding stabilizes the VP35 N-terminal oligomerization domain and enhances viral RNA synthesis. Mutational analysis demonstrates that VP35 interaction is required for the functional effects of LC8.